Coordination of thermal/wind energies in power-to-gas process for cost/pollution abatement considering wind energy recovery. Issue 1 (31st March 2022) - Hemmati, Reza; Nosratabadi, Seyyed Mostafa; Mehrjerdi, Hasan; Bornapour, Mosayeb
ABSTRACT: This paper utilizes the thermal and wind energies in power to gas (P2G) process. The purpose of the proposed P2G system is to reduce the operating costs and environmental pollutions. The wind energy is used to produce Hydrogen (H2 ) via water electrolyzer. The Carbon dioxide (CO2 ) of thermal energies is also captured by Carbon Capture and Storage (CCS). The achieved H2 and CO2 are combined to make Methane (CH4 ) through Methanation reaction. The unit commitment denotes the optimal operation schedule of thermal generating units at each hour. The proposed model also determines the optimal size of wind energy. In the case of any event or outage, the wind energy recovery is studied by application of hybrid battery-capacitor storage system. The achieved CH4 from wind energy is sold to make profit. The wind speed volatility is included in the model and handled by stochastic programming. The proposed P2G achieves several purposes including optimal wind turbine sizing, uncertainty management, CO2 decrease and operating cost reduction. It is demonstrated that the Carbon tax can reduce the CO2 pollutions up to 8%. The high-cost and high-polluting generating systems like oil fired steam turbines are only used at on-peak hours like 17–21. These units produce about 6% of total energy but releases 11% of total CO2 . The optimal capacity of wind generating system is obtained equal to 107 MW and the profit of process is estimated about 2.383 million $ in year.